Anterior Colporrhaphy Technique and Approach Choices: Turkey Evaluation - Serdar Aydın; Rabia Zehra Bakar; Gonca Batmaz; Mahinur Betül Çalışkan; Çağrı Arıoğlu Aydın (Haseki Tıp Bülteni)
Aim: To evaluate the diversity in techniques and approaches for anterior colporrhaphy among operators in Turkey. Methods: A survey evaluating the preoperative examination, technique of anterior colporrhaphy, operation choice and postoperative care was presented to surgeons. We contacted via directly, mail or telephone. We used 28 item questionnaire. Results: Majority (87.9%) was composed of young gynecologists. Urologists composed of the 9.5% of the study population. The rate of paravaginal defect evaluation was 75.9% and mostly by inspection the presence of vaginal rugae. The use of transperineal 3D pelvic floor ultrasonography was low (5.7%). The evaluation of levator ani muscle defect was 46.6%. The usage of the transperineal 3D ultrasonography for levator ani muscle defect was 19 percent of operators. There were diversity in use of hydrodissection, fascial plication, excision of vaginal mucosa and suture choice. Usage of mesh for anterior colporrhaphy was limited (17.8%) and mostly in recurrent cases (12.2%). Paravaginal defect repair rate was 31.9%. The urinary catheter was generally removed one or two day after operation. Vaginal pack usually removed 24 hours after. Conclusion: Several techniques and approaches for anterior vaginal wall repair among operators in Turkey. The variety of techniques suggested that there is no consensus on best surgical technique.